The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1040638716637639
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and molecular characterization of Edwardsiella piscicida infection in largemouth bass (Micropterus salmoides)

Abstract: The genus Edwardsiella is composed of a diverse group of facultative anaerobic, gram-negative bacteria that can produce disease in a wide variety of hosts, including birds, reptiles, mammals, and fish. Our report describes the isolation and identification of Edwardsiella piscicida associated with chronic mortality events in 2 separate captive largemouth bass ( Micropterus salmoides) populations in New York and Florida. Wet-mount biopsies of skin mucus, gill, kidney, and spleen from several affected largemouth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 27 publications
3
24
0
1
Order By: Relevance
“…The inflammatory response observed in the periocular tissue, epicardium, coelomic adipose and gill supports systemic dissemination of bacterial organisms and/or their toxic products likely via a hematogenous route. While not pathognomonic for piscine Edwardsiellosis, the hyperplastic and necrotizing branchitis are consistent with reports of E. piscicida infection in other temperate, freshwater fishes (Fogelson et al, ; Griffin et al, ; Camus, Griffin, Armwood, & Soto, ).…”
Section: Primer and Probe Sequencessupporting
confidence: 88%
“…The inflammatory response observed in the periocular tissue, epicardium, coelomic adipose and gill supports systemic dissemination of bacterial organisms and/or their toxic products likely via a hematogenous route. While not pathognomonic for piscine Edwardsiellosis, the hyperplastic and necrotizing branchitis are consistent with reports of E. piscicida infection in other temperate, freshwater fishes (Fogelson et al, ; Griffin et al, ; Camus, Griffin, Armwood, & Soto, ).…”
Section: Primer and Probe Sequencessupporting
confidence: 88%
“…Reports of bacterial disease are limited primarily to common freshwater pathogens, such as Aeromonas hydrophila (Huizinga, Esch, & Hazen, ) and Flavobacterium columnare (Mohammed & Arias, ). In addition, fish kills and systemic infections in recirculating culture systems have been attributed to Edwardsiella tarda (Francis‐Floyd, Reed, Bolon, Estes, & McKinney, ) and Edwardsiella piscicida (Fogelson et al, ), respectively.…”
Section: Antibiotic Minimum Inhibitory Concentrations (Mic) Against Tmentioning
confidence: 99%
“…Lesions reflect the multifocal organ necrosis, granuloma formation and progressive granulomatous inflammation described with E. piscicida infection in largemouth bass by Fogelson et al (2016). The fish were in excellent physical condition with no known stressors identified, suggesting the bacterium was acting as a pri- (Miyazaki & Plumb, 1985).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Recent investigations into its heterogeneity revealed that this previous classification actually encompassed three genetically distinct, yet phenotypically ambiguous, taxa, namely, E. tarda , E. piscicida , and E. anguillarum (7, 8). Edwardsiella piscicida has since been isolated from a variety of diseased wild and cultured fish (912). Recent studies demonstrated that E. piscicida is more virulent to channel catfish than E. tarda or E. anguillarum and is increasingly recovered from diseased farm-raised catfish in the southeastern United States (13, 14).…”
Section: Genome Announcementmentioning
confidence: 99%